Masoretic Forensics and Scribal Fingerprints - Phillips, Kim (Vetus Testamentum, 2025)
In recent years three bilingual Hebrew-Judaeo-Arabic Torah manuscript fragments have been tentatively identified as the work of the scribe Samuel b. Jacob (best-known for his production of the so-called Leningrad Codex): CUL T-S Ar.1a.2+; RNL EVR II A 640; Oxf. MS heb. f. 108/3. These identifications were made on the basis of script similarity alone. This study, premised on the work of the great Hebrew codicologist Malachi Beit-Arié, demonstrates that all three of these manuscripts have been mis-identified. Thereby, the study affirms Beit-Arié’s claim that, at least in the case of early Eastern Hebrew Bible codices, scribal identifications should not be made on the basis of script alone, but on a raft of textual and paratextual scribal features that remain demonstrably stable across a given scribe’s oeuvre.